Socio-emotional Skills and Graduate Employability in the Hospitality Sector of South Western Uganda, Kigezi Sub -Region. - Tushabe, Sylivia Byarugaba; SSempala, Fredrick; Ampumuza, Christine; Mbowa, Henry Stanley (Kabale University, 2024)
Hospitality graduates struggle to secure employment in the hospitality sector. This study examined the relationship between socio-emotional skills and graduate employability in the hospitality sector in the southwest Uganda-Kigezi sub-region. The research design employed in this study was the cross-sectional quantitative research design with a population of 640 graduates and a sample size of 400 was established for hospitality graduates based on Krejcie and Morgan’s (1970). The data was collected using structured and unstructured questionnaires and the data analysis was done by SPSS V. 23 Smart PLS V 4 and NVivo. Socio-emotional skills like emotional intelligence, teamwork, and communication skills were found to affect graduate employability. Numerous barriers were pointed out, like lack of experience and limited chance to meet others. Based on the study findings call for focusing on practical training and internships with institutions and industries to acquire skills required for improvement in the job market. Recommendations included curriculum integration, industry collaboration, practical experience internships and apprenticeships, and creating a linkage between HEIs and the hospitality sector. Furthermore, the development of socio-emotional skills is a prerequisite for the development of employment in the hospitality sector. This study may contribute to the existing literature on the development of soft skills and employment, and the findings from this study may be helpful for analogous study environments in Southwestern Uganda—Kigezi Sub-Region.